The effort for a better administration of Islamic religious affairs and the harmonization of Islamic laws in Malaysia - Mokhtar, Khairil Azmin (2007)
The predicament of Islamic religious laws and its administration have been one of the concerns of both federal and state governments in Malaysia. It is accepted fact that existence of different laws and religious bureaucracies is inevitable because within the constitutional framework of the country Islamic religious powers are vested in the state governments and associated with constitutional power and traditional role of the Malay Rulers in their respective states. The focus of the paper is on efforts made to improve some aspects of religios administration and to harmonise Islamic religious laws of the states. Observation in this article is made from constitutional perspective with emphasis on federalism.